Expanding the mutation spectrum of the MTM1 gene: the first multi-exonic duplication and establishment of the MTM1 locus-specific database - Oliveira, Jorge (2012)
Centronuclear myopathies (CNM) are a group of diseases with variable onset and severity sharing as a distinctive histological feature, a high frequency of muscle fibers with centralized nuclei. Myotubular myopathy (MIM#310400) the X-linked form of CNM is characterized by neonatal hypotonia and inability to maintain unassisted respiration. The MTM1 gene, responsible for this disease, encodes myotubularin, a protein involved in myofiber differentiation and muscle cell architecture. In this work, eight patients were subjected to MTM1 MLPA analysis, selected according to the following criteria: (i) muscle biopsy compatible with CNM and (ii) exclusion of MTM1 point mutations by sequencing. We identified the first gross duplication spanning exons 1–5 (c.-76-?_342+?dup) in a 7 year old boy with progressive tetraparesis, ophtalmoparesis, facial diparesis and independent ambulation, the clinical course being milder than the classical myotubular myopathies. Analysis at the mRNA level revealed both normal transcripts and a mutated isoform lacking exon 6 (r.343_444del), suggesting somatic mosaicism. As suspected, this duplication was not detected in the patient’s mother. Considering the phenotypic expression in the patient, this mutational event most likely occurred de novo during early embryogenesis. We also describe the implementation of a locus-specific database (LSDB) for this gene using the Leiden Open Variation database (LOVD) software. The MTM1-LOVD (http://www.lovd.nl/MTM1) contains 372 mutation entries identified in 370 patients (last accessed March 2011). A total of 223 unique MTM1 mutations are listed in this LSDB, including: 207 point mutations, 15 single or multi-exonic deletions and the large duplication described in the present work. Despite the significant advances in this field during the last decade about one third of the CNM cases remain genetically unresolved. Here we show that gross MTM1 gene duplications may account for a fraction of these cases.